Implementation of the Merdeka Curriculum through Islamic Religious Education Learning Based on the 8 Dimensional Graduate Profile - Sholekhah, Linda Ayu; Inayati, Nurul Latifaul (Universitas Muhammadiyah Surakarta, 2025)
This study examines the implementation of the 8 Dimensional Graduate Profile in Islamic Religious Education (PAI) learning within the Merdeka Curriculum at State Junior High School 1 Surakarta. The aim is to analyze the application of this Profile in PAI teaching practices and identify the challenges faced by teachers. The research employs a qualitative method with a field study design, utilizing interview techniques, observation, and document analysis. The findings reveal that the 8 Dimensional Graduate Profile is not taught as an independent subject but is integrated through active learning, religious practices, collaborative activities, and school habituation programs. This implementation supports the development of students' religious character, independence, cooperation, communication skills, and health awareness. The identified challenges include limitations in instructional time allocation and student diversity, which affect the optimization of teacher guidance. This research affirms the importance of holistic and contextual PAI learning within the framework of the Merdeka Curriculum for shaping students with character and competitiveness.